Assembly of 3D flower-like NiO hierarchical architectures by 2D nanosheets: synthesis and their sensing properties to formaldehyde. Issue 6 (13th January 2017) - San, Xiaoguang; Zhao, Guodong; Wang, Guosheng; Shen, Yanbai; Meng, Dan; Zhang, Yajing; Meng, Fanli
Abstract : NiO flower-like hierarchical architectures were synthesized by a solvothermal route, which exhibited good formaldehyde gas sensing performance. The effect of reaction time and ethanol/water volume ratio on morphologies was investigated and a synthesis mechanism was proposed. Abstract : Flower-like NiO hierarchical architectures were synthesized by a solvothermal process without using any other surfactant. Absolute ethanol and distilled water were adopted as solvent, and nickel nitrate hexahydrate was employed as the nickel source. The morphology and crystal structure were mainly investigated. Through annealing the as-obtained products, flower-like NiO hierarchical architectures with a cubic structure were synthesized, which were assembled by a number of thin nanosheets with a thickness of about 30 nm. The formaldehyde gas sensing measurements showed that well-defined NiO flower-like structures with large surface area exhibited higher responses compared with microsheets/nanosheets at a relatively lower operating temperature of 200 °C. Moreover, a reversible and fast response to formaldehyde gas at various gas concentrations, good selectivity and stability were obtained. The results indicated that the flower-like NiO hierarchical architectures are promising materials for gas sensors.